2014
DOI: 10.1161/atvbaha.114.303034
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Fat, Insulin Resistance, and Nonalcoholic Fatty Liver Disease

Abstract: Ectopic fat accumulation in the liver causes nonalcoholic fatty liver disease (NAFLD), which is the most common cause of chronic liver disease in Western countries. Ectopic liver lipid, particularly diacylglycerol, exacerbates hepatic insulin resistance, promotes systemic inflammation, and increases risk of developing both type 2 diabetes mellitus and cardiovascular disease. Increasing evidence suggests that NAFLD is an emerging risk factor for cardiovascular disease, and although there are currently no licens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 67 publications
2
94
0
6
Order By: Relevance
“…In fact, 65% of individuals with MetS accompanied with fatty liver in this study population. Both NAFLD [27] and MetS [28] are associated with insulin resistance. Visceral fat secretes inflammatory adipokines, such as interleukin-6, tumor necrosis factor-α and macrophage chemoattractant protein-1, which leads to insulin resistance [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, 65% of individuals with MetS accompanied with fatty liver in this study population. Both NAFLD [27] and MetS [28] are associated with insulin resistance. Visceral fat secretes inflammatory adipokines, such as interleukin-6, tumor necrosis factor-α and macrophage chemoattractant protein-1, which leads to insulin resistance [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NAFLD has a close association with ectopic fat [31]. Ectopic fat, which has close association with organ-specific insulin resistance via a process termed 'lipotoxicity' [32], is one of the major causes of type 2 diabetes [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this complex situation, the liver may function both as the target organ of the resulting systemic abnormalities (induced by expanded visceral adipose tissue) and the source of several pathogenic mediators that may amplify the cardiac and vascular damage. Indeed, NAFLD, especially its necro-inflammatory variant, may exacerbate insulin resistance and releases a myriad of pro-inflammatory factors and vasoactive and thrombogenic molecules that play important roles in the development and progression of LVDD and structural cardiac diseases [1,[6][7][8][9]39]. Preliminary evidence also suggests that patients with NAFLD have changes in cardiac substrate metabolism that may produce myocardial functional and structural abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rijzewijk et al [40] found that uncomplicated type 2 diabetic male patients with higher intra-hepatic triglyceride content on proton magnetic resonance spectroscopy had higher myocardial insulin resistance, lower myocardial high-energy phosphate metabolism (as measured by the phosphocreatine/adenosine triphosphate ratio) and lower myocardial perfusion compared with their counterparts with lower intra-hepatic triglyceride content; notably, these abnormalities in myocardial substrate metabolism were more severe among those with higher intra-hepatic triglyceride content even after adjustment for potential confounders [40]. Emerging evidence also suggests that the coexistence of obesity-related increases in fat accumulation in the myocardium/pericardium might additionally exert local adverse effects that result in functional and structural cardiac alterations [9,38,39]. Rijzewijk et al [41] found that myocardial steatosis was much higher in uncomplicated type 2 diabetic male patients with preserved systolic function than in age-and BMI-matched healthy controls, and that higher intra-myocardial triglyceride content was associated with LVDD, independently of age, BMI, visceral adipose tissue, heart rate and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Preliminary evidence also suggests that GD is associated with more severe liver damage in NAFLD patients. 17 Additionally, some populationbased studies also reveal a significant association between NAFLD and cholecystectomy, but no association between NAFLD and gallstones, 18,19 suggesting that cholecystectomy might not be innocuous and may contribute to NAFLD development and progression.…”
Section: Arterioscler Thromb Vasc Biol October 2015mentioning
confidence: 99%